Uma aproximação cética à relação entre epistemologia e direito - Herrera Pérez, Enlil Iván (2021)
In this article the author presents the main concepts related to epistemology, science and the search for truth from the perspectives of Bunge, Tarski, Popper and Kuhn. Concepts that relates to an instrumental notion of law. All this with the aim of answering the question of whether or not there is a relationship between epistemology and law, and about what kind of relationship would exist. On this basis, and with a skeptical approach, it concludes by highlighting the relevance of science and law.